The Effectiveness of Using Google Classroom On Students Achievement In Learning English - Siti Julaida Siregar; Yani Lubis (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this research was to investigate the impact of Google Classroom on the learning achievements of English language students at State Islamic University Of North Sumatra Medan. This form of research is a pre-experiment with the research design, specifically the One Group Pretest Posttest Design. The participants in this study were students in the eighth semester of the 2020 English Language Education Study Program. The independent variable in this study is online learning, while the bound factors are student learning outcomes. Methods for data collecting include distributing the questionnaire employed the G form, which was organized using the Likert scale approach. According to the research findings, respondents' final competence tests vary greatly based on the completion criteria. The validity test demonstrates that all indicator items are valid. The findings of the reliability test for the entire variable are reliable. The normality test indicates that all data is normal. The research instrument consisted of 30 multiple-choice questions. Data collecting strategies include pretesting and posttesting. The gathered data is then examined statistically, both descriptively and inferentially, using the SPSS 25 program. The results showed that the average pretest value was 40, while the average posttest value was 80. The independent sample analysis T test yielded a significance value of p = 0.000 <α = 0.05. As a result, it is possible to establish that online learning influences student learning results.